Dr. Seuss went to war : a catalog of political cartoons (2007)
[Dt.:] Die Online-Ausstellung zeigt 200 Karikaturen von Theodor Seuss Geisel (1904-1991). Sie entstanden zwischen 1941 und 1943 für das PM Magazin. Theodor Seuss Geisel war ein US-amerikanischer Kinderbuch-Autor und Cartoonzeichner, bekannt unter seinem Künstlernamen Dr. Seuss. Die Karikaturen sind chronologisch geordnet. Zudem sind sie über Themen und Namen recherchierbar. - [Engl.:] The website presents 200 political cartoons by Theodor Seuss Geisel (1904-1991) penned from 1941-1943 in the New York newspaper PM. He was an American writer and cartoonist known for his classic children's books under the pen name Dr. Seuss. The PM cartoons in the website are arranged in chronological order, by year, by month, by day. The images are also browsable by subject terms.